Radiographic evaluation of the prevalence of dental anomalies of number - Gonçalo D. Costa; Pedro Mesquita (Sociedade Portuguesa de Estomatologia e Medicina Dentária, 2023)
Objectives: This study aims to determine the prevalence of tooth agenesis and supernumerary teeth and characterize both anomalies in a Portuguese pediatric population. Methods: Clinical records of patients attending Pediatric Dentistry appointments in the Faculty of Dental Medicine of the University of Porto were consulted. Appointments from September 2020 to December 2021 were analyzed. For each patient, sex and age were recorded, along with any relevant data in their clinical history. Statistical analysis of the results was conducted using chi-square tests with a significance level of 0.05. The sample included 144 patients. Results: This study found a prevalence for tooth agenesis of 20.83% (11.81% excluding the third molars) and a prevalence for supernumerary teeth of 1.39%. The prevalence of agenesis was 26.1% for males and 16% for females. No association was established in this regard (p>0.05). The most affected teeth were the third molars, followed by the second premolars. The mandible had 52.63% of agenesis cases, but no association was found (p>0.05). Two cases of supernumerary teeth were found, both in male patients and in the second quadrant. No differences were inferred regarding sex (p>0.05). Conclusions: The results of this study contributed to the existing data regarding the prevalence of dental anomalies of number within a Portuguese population.